Differences in Return of Spontaneous Circulation in Early vs Late Endotracheal Intubation among Patients in Hospital Cardiac Arrest - Shrestha, Battu Kumar; Sharma, Apurb; Gyawali, Parbesh Kumar (Journal of Nepal Health Research Council, 2018)
Background: Common airway management strategies during cardiopulmonary resuscitation are bag- mask-valve ventilation followed by endotracheal intubation. Timing of endotracheal intubation is controversial. This study was designed to compare the effect of early vs late endotracheal intubation in terms of return of spontaneous circulation.Methods: This is an observational retrospective study done at tertiary center for the period of two years. The study population was inpatient, adult and pediatric with witnessed cardiac arrest in whom airway management was initially done with bag-valve-mask ventilation followed by endotracheal intubation. Timing of intubations were grouped into early and late with cut off time of five minutes and the groups were compared in terms of return of spontaneous circulation.Results: There were total of 193 patients included in the study. Early intubation was done in 114 patients (59.06%) and late intubation was done in 79 patients (40.94%). Mean time for early intubation was 3.11 minutes. Mean time for late intubation was 7.89 minutes. Seventy three patients (37.8%) attained sustained ROSC. Thirty five patients (30.7%) achieved ROSC in early intubation group while 38 patients (48.1%) attained sustained ROSC in late intubation group(p = 0.016). Conclusions: Early intubation during cardiopulmonary resuscitation was associated with lower rate of return of spontaneous circulation.